2021
DOI: 10.1186/s12889-021-12151-3
|View full text |Cite|
|
Sign up to set email alerts
|

Disclosure of same-sex practices and experiences of healthcare stigma among cisgender men who have sex with men in five sub-Saharan African countries

Abstract: Background For men who have sex with men (MSM) across sub-Saharan Africa (SSA), disclosure of same-sex practices to family and healthcare workers (HCWs) can facilitate access to HIV prevention services and support, but can also lead to experiences of stigma. Methods We performed mixed-effects regressions on pooled data from MSM in Cameroon, Senegal, Côte d’Ivoire, Lesotho, and eSwatini to assess associations between disclosure and sexual behavior s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 67 publications
2
9
0
Order By: Relevance
“…A study of MSM in Cameroon, Côte d’Ivoire, Eswatini, Lesotho, and Senegal found that MSM who had disclosed their sexuality to health-care workers were more likely to express fear of health services, avoid health services, face gossiping by health-care workers, and feel mistreated in the health centre. 74 These findings align with minority stress theory by revealing adverse interpersonal consequences, such as stigma and shame, for MSM who disclose their sexuality in unsupportive medical environments, which can ultimately result in avoidance of and disengagement with health care. Consistent with syndemic framework, studies in several African countries have shown synergistic links between HIV, mental health, and contextual inequalities among MSM.…”
Section: Evidence Of Multilevel Determinants Of Hiv and Mental Health...supporting
confidence: 68%
“…A study of MSM in Cameroon, Côte d’Ivoire, Eswatini, Lesotho, and Senegal found that MSM who had disclosed their sexuality to health-care workers were more likely to express fear of health services, avoid health services, face gossiping by health-care workers, and feel mistreated in the health centre. 74 These findings align with minority stress theory by revealing adverse interpersonal consequences, such as stigma and shame, for MSM who disclose their sexuality in unsupportive medical environments, which can ultimately result in avoidance of and disengagement with health care. Consistent with syndemic framework, studies in several African countries have shown synergistic links between HIV, mental health, and contextual inequalities among MSM.…”
Section: Evidence Of Multilevel Determinants Of Hiv and Mental Health...supporting
confidence: 68%
“…Disclosure, for instance, has been linked to instances of sexual behavior stigma in both family and friends, and within healthcare settings, and by association may impact comfortability in HIV prevention and testing. In a recent study conducted among five SSA countries, 50 MSM who disclosed their same-sex sexual behaviors to both family members and healthcare workers (as compared to MSM who had disclosed to neither) were more likely to both express being afraid of and to avoid seeking out health services due to the possibility someone could learn that that they have sex with men. They also had more than three times the odds of reporting a healthcare worker had gossiped about them and of feeling mistreated at a health center if they had disclosed to both with a smaller association observed for those who had only disclosed to healthcare workers.…”
Section: Discussionmentioning
confidence: 98%
“…While the peer approach has successfully identified KPs with high HIV testing yield and linkage to treatment, stigma and discrimination can still have a demonstrative impact on engagement in care. Fear of stigma plays a major role in KPs’ hesitancy to access healthcare services, as they fear that they will be condemned by HCWs [ 44 ]. Retaining and recruiting experienced CHWs can be a barrier to programme implementation, and these difficulties may be explained by high mobility, stigma and community discrimination [ 45 ].…”
Section: Discussionmentioning
confidence: 99%